(untitled) (Indian Journal of Experimental Biology (IJEB), 2026)
Urgently needed new antimicrobial strategies due to antibiotic resistance. This study aimed to develop and evaluate green-synthesized silver nanoparticles (AgNPs) with Aloe vera leaf extract as a low-cytotoxic, safe method to boost innate immunity. The nanoparticles were characterized by TEM, showing spherical particles 15–25 nm in size with a zeta potential of −28.6 mV, indicating high colloidal stability. UV–Vis analysis displayed a clear surface plasmon resonance peak at 420 nm. The murine macrophage cell line RAW 264.7 was used to assess cytocompatibility and immunostimulatory activity through nitric oxide release and cytokine (TNF-α, IL-6) production. Assays for macrophage clearance, minimum bactericidal concentration (MBC), and minimum inhibitory concentration (MIC) were conducted to evaluate antibacterial effectiveness against Staphylococcus aureus and Escherichia coli. The biosynthesized AgNPs maintained macrophage viability, increased pro-inflammatory cytokine and nitric oxide production at non-toxic levels, and exhibited strong antibacterial activity with low MIC and MBC values. Green-synthesized AgNPs can serve as effective, low-toxicity agents combining antimicrobial and immune-stimulating properties to help combat antibiotic resistance, as demonstrated by the enhanced bacterial clearance shown by treated macrophages.